THE MEASUREMENT ELECTROMAGNETIC INTERFERENCE IN THE REVERSE TRACTION NETWORK - Serdiuk, T. M.; Zavhorodnii, O. V.; Havryliuk, V. I. (Science and Transport Progress, 2009)
The original automated method of measurement of electrical noise in the return electric-traction network is proposed. It is realized on the base of car-laboratory “Automatics, telemechanics and communication”. The mathematic model of return electric-traction network is developed to scientific bases of automated measurement. It allows us obtaining the mathematic expressions for change of voltage and current harmonics in the rail net and taking into account the inhomogeneity of lines for the following analytic determination of a source of electric noise.